Effects of the "live high-train high" and "live high-train low" protocols on physiological adaptations and athletic performance - Muraoka, I.; Gando, Y. (The Journal of Physical Fitness and Sports Medicine, 2012)
The present article reviews the effects of the traditional "live high-train high" (LHTH) protocol and the contemporary "live high-train low" (LHTL) protocol on physiological adaptations and on athletic performance at sea level based on results from studies in which athletes were assigned to an "altitude group" and "sea level group". Consequently, the LHTH protocol and LHTL protocol were considered to provoke nearly similar physiological adaptations. On the other hand, the LHTL protocol appeared to be more effective than the LHTH protocol with respect to endurance performance at sea level. Furthermore, the LHTL protocol is suggested to possibly be effective for sprinting events as well. These results indicate that the LHTL protocol affords about 1 to 4% improvement in exercise of approximately 30-second to 17-minute duration. However, a recent meta-analysis suggested that the LHTH protocol improves the maximal power output of elite athletes. Furthermore, it is conceivable that interindividual differences greatly affect the results obtained from altitude training. Therefore, there is an urgent need to elucidate interindividual differences that are involved in physiological adaptations to hypoxic environments or improvements in athletic performance. Moreover, the relevant elucidation will require the adjustment of altitude (oxygen concentration), daily duration of exposure, and length of stay in concert with individual features. In some cases, a decision about whether or not to adopt the LHTL or LHTH protocol would be necessitated. In addition, the combination of the intermittent hypoxic training protocol with the LHTL protocol will require a detailed investigation.